Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan pada PT. Duta Raja Gas Depok (International Forum of Researchers and Lecturers, 2025)
Human resource management is a branch of management science that specifically focuses on managing interactions between individuals in a company or institution. Employee management is a challenge in itself, because each individual brings different characteristics, potentials and backgrounds. This study aims to determine the influence of leadership style and organizational culture on employee performance. In this study, the researcher used quantitative statistical analysis, multiple linear regression analysis and determination coefficient analysis with the help of IBM SPSS software version 21. The sample used in this study was a saturated sample of 40 employees. The results of this study were obtained using the t-test that leadership style partially had a positive and significant effect on employee performance with a significance level of 0.018 < 0.05 and the t-test results were 2.477 > 2.026. Organizational culture partially had a positive and significant effect on employee performance with a significance level of 0.001 < 0.05 and the t-test results were 3,530 > 2.026. Leadership style and Organizational culture simultaneously have a positive and significant effect with a significance level of 0.000 < 0.05 and the F test results are 12,692 > 3.25 on employee performance.